Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How would you compute the following series? I'm interested in some easy approaches that would allow me to work it out. $$\sum_{n=1}^{\infty} \frac{4^n n!}{(2n)!}$$

share|improve this question
    
Try the Laplace transform approach. –  Mhenni Benghorbal Feb 21 '13 at 16:37
    
@MhenniBenghorbal: Does Laplace work here? Interesting! Thank you for your precious feedback! –  Chris's sis Feb 21 '13 at 16:44
    
I have not worked out. Just try to follow the technique and see what you get. I'll try to do this later. –  Mhenni Benghorbal Feb 21 '13 at 16:47
    
@MhenniBenghorbal: I saw the post. It's really precious that way. –  Chris's sis Feb 21 '13 at 18:18
add comment

3 Answers

up vote 18 down vote accepted

It suffices to calculate the sum with the summation index running from 0, not from 1. Then

$$\begin{align*} \sum_{n=0}^{\infty} \frac{4^n n!}{(2n)!} &= \sum_{n=0}^{\infty} \frac{4^n}{(2n)!}\int_{0}^{\infty}t^n e^{-t}\;dt\\ &= \int_{0}^{\infty}\sum_{n=0}^{\infty} \frac{4^n t^n}{(2n)!} e^{-t}\;dt\\ &= \int_{0}^{\infty} \cosh(2\sqrt{t}) e^{-t}\;dt\\ &= \int_{0}^{\infty} 2u\cosh(2u) e^{-u^2}\;du\qquad(t=u^2)\\ &= \left[-\cosh(2u)e^{-u^2}\right]_{0}^{\infty} + 2\int_{0}^{\infty} \sinh(2u) e^{-u^2}\;du\\ &= 1 + 2\int_{0}^{\infty} \sinh(2u) e^{-u^2}\;du \\ &= 1 + \int_{0}^{\infty} \left(e^{2u} - e^{-2u}\right) e^{-u^2}\;du \\ &= 1 + e \int_{0}^{\infty} \left(e^{-(u-1)^2} - e^{-(u+1)^2}\right)\;du. \end{align*}$$

Now it is clear how to express the last integrals in terms of the error function, yielding

$$ \sum_{n=1}^{\infty} \frac{4^n n!}{(2n)!} = e\sqrt{\pi} \mathrm{erf}(1).$$

share|improve this answer
    
+1 nice $ $ $ $ –  draks ... Aug 7 '12 at 6:56
    
Good answer! Thanks! –  Chris's sis Aug 7 '12 at 7:03
add comment

Here is a generalization. Consider the generating function

$$f(x) = \sum_{n \ge 1} \frac{x^{2n} n!}{(2n)!}.$$

It's an easy check that $2$ is in the radius of convergence, so that we need to compute $f(2)$ to solve your problem. However, it's easy to see that

$$f''(x) = 1 + \sum_{n \ge 1} \frac{x^{2n} (n + 1)!}{(2n)!}$$

Moreover,

$$xf'(x) = 2 \sum_{n \ge 1} \frac{x^{2n} n!}{(2n)!} \cdot n$$

We get the second-order ODE

$$\frac{xf'(x)}{2} + f(x) = f''(x) - 1, f(0) = 0, f'(0) = 0.$$

And the solution

$$f(x) = \frac{1}{2} \cdot e^{x^2/4} \cdot x \sqrt{\pi} \mathrm{erf}(x/2).$$

Just plug in $x = 2$ to get your answer, $e\sqrt{\pi} \mathrm{erf}(1)$.

share|improve this answer
    
mersi fain pentru solutia oferita. (Thank you!) –  Chris's sis Aug 7 '12 at 13:25
add comment

This is not an appropriate answer. We have $n!\approx C n^{n+1/2}e^{-n}$, so the terms become approximate $$4^{n}\frac{C n^{n}n^{1/2}e^{-n}}{C 2^{2n}2^{1/2}n^{2n}n^{1/2}e^{-2n}}$$

After cancelling out the terms we should have $$\frac{1}{2^{1/2}e^{-n}n^{n}}=2^{-1/2}(\frac{e}{n})^{n}$$

I do not know if there is any way to sum $$C\sum^{\infty}_{N}(\frac{e}{n})^{n}$$ where $N$ is some very large number depends on Stirling's formula. Now suppose we have $kn,0\le k\le 1$ instead of $e$. Then we should have $$\sum^{\infty}_{N}k^{n}=\frac{k^{N}}{1-k}$$

So obviously for fixed $N$ we have the top side of the derivative to be $$Nk^{N-1}(1-k)+k^{N}=Nk^{N-1}-(N-1)k^{N}$$ which equals 0 if and only if $$k=\frac{N}{N-1}$$ which is impossible by our assumption on $k$. Thus this sum increases monotone with $k$ and has a minimum at $k=0$. So assume $k=\frac{e}{N}$ we should be able to bound the original sum from above. For the exact value one probably need to run a computer program.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.